Micro Influencer Strategy in Building Public Trust in the Emina Brand - Adelia Rahmadani; Zuhriah Zuhriah (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2026)
The rapid growth of digital communication and social media has transformed marketing communication strategies, encouraging companies to utilize micro influencers to establish stronger relationships with consumers. Unlike conventional promotional approaches, micro influencers are considered more credible, authentic, and capable of fostering public trust through interactive communication. This study aims to analyze the communication strategies employed by micro influencers in building public trust toward the Emina cosmetic brand on social media. The research adopted a qualitative descriptive approach. Data were collected through in-depth interviews with two micro influencers and their followers, supported by social media content observation and documentation. The data were analyzed using the interactive model of data reduction, data display, and conclusion drawing. The findings reveal that public trust is developed through five key communication strategies: influencer credibility, message authenticity, two-way communication and audience engagement, congruence between the influencer and the Emina brand, and consistency in delivering content. These elements collectively create emotional connections, enhance message credibility, and encourage positive audience perceptions of the brand. The study also demonstrates that followers place greater trust in product recommendations based on genuine personal experiences rather than purely promotional content. This research contributes to the development of digital marketing communication studies by providing a comprehensive qualitative understanding of how micro influencers shape public trust and offers practical insights for brands targeting Generation Z consumers through social media.